The Pengaruh Transformational Leadership dan Quality of Work Life Terhadap Organizational Citizenship Behavior (OCB) Dimediasi Commitment Organizational Pada PT Rumah Bersama Seluler - Fathehah, Vannesya Alif Nur; Subiyanto, Didik; Yulianto, Eko (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The$ curre$nt e$ra of globalization incre$ase$s compe$tition in incre$asingly compe$titive$ companie$s and re$quire$s companie$s to improve$ innovation. The$ purpose$ of this study is to analyze$ the$ influe$nce$ of transformational le$ade$rship and quality of work life$ on Organizational Citize$nship Be$havior (OCB) with organizational commitme$nt as a me$diating variable$ in PT Rumah Be$rsama Se$lule$r. This study use$s a quantitative$ approach with data colle$cte$d through que$stionnaire$s. The$ re$se$arch sample$ include$s all e$mploye$e$s of PT Rumah Be$rsama Se$lule$r, which is 98 re$sponde$nts. The$ re$sults of the$ analysis of this study show that all hypothe$se$s are$ acce$pte$d, name$ly transformational le$ade$rship and quality of work life$ affe$ct organizational commitme$nt and organizational citize$nship be$havior. The$ variable$ of organizational commitme$nt also affe$cts organizational citize$nship be$havior. This shows that e$mploye$e$s who have$ a high quality of work life$ and organizational commitme$nt, can incre$ase$ e$mploye$e$ OCB. The$ implications of this study are$ important for PT Rumah Be$rsama Se$llular in incre$asing the$ role$ of OCB e$mploye$e$s by incre$asing the$se$ factors